2021
DOI: 10.2147/ijgm.s342597
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Clinical Significance of Origin Recognition Complex Subunit 6 in Breast Cancer – A Comprehensive Bioinformatics Analysis

Abstract: Objective We aimed to investigate the expression, diagnostic and prognostic values, and potential molecular mechanisms of the origin recognition complex (ORC) in breast cancer (BC). Methods Kaplan–Meier estimation was used to assess the prognostic value of ORC genes, and Oncomine, TCGA, GEO and ULCAN databases were used to analyze their expression in BC. Wilcoxon rank-sum tests were used to evaluate the relationship between ORC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…L3MBTL3, a member of the putative polycomb group (PcG) protein family, is thought to be associated with cancer risk [47]. Meanwhile, we discovered a strong connection between the Origin Recognition Complex (ORC) gene family and various cancer types [48,49]. However, researchers have paid little attention to ORC2 and its role in cancer progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…L3MBTL3, a member of the putative polycomb group (PcG) protein family, is thought to be associated with cancer risk [47]. Meanwhile, we discovered a strong connection between the Origin Recognition Complex (ORC) gene family and various cancer types [48,49]. However, researchers have paid little attention to ORC2 and its role in cancer progression and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…ORC6 is a cofactor in the mismatch repair (MMR) complex that promotes efficient mismatch repair (8). In recent years, research has identified a correlation between elevated ORC6 expression and adverse prognostic outcomes in patients with colorectal cancer (9), renal clear cell carcinoma (10), gastric adenocarcinoma (11), and breast cancer (12). Current research on ORC6 in tumors is restricted to specific types of human cancers.…”
Section: Introductionmentioning
confidence: 99%